The iron deficiency response in Arabidopsis thaliana requires the phosphorylated transcription factor URI - Kim, Sun A.; LaCroix, Ian S.; Gerber, Scott A.; Guerinot, Mary Lou (Proceedings of the National Academy of Sciences - PNAS, 2019)
Iron is an essential nutrient for plants, but excess iron is toxic due to its catalytic role in the formation of hydroxyl radicals. Thus, iron uptake is highly regulated and induced only under iron deficiency. The mechanisms of iron uptake in roots are well characterized, but less is known about how plants perceive iron deficiency. We show that a basic helix–loop–helix (bHLH) transcription factor Upstream Regulator of IRT1 (URI) acts as an essential part of the iron deficiency signaling pathway in Arabidopsis thaliana. The uri mutant is defective in inducing Iron-Regulated Transporter1 (IRT1) and Ferric Reduction Oxidase2 (FRO2) and their transcriptional regulators FER-like iron deficiency-induced transcription factor (FIT) and bHLH38/39/100/101 in response to iron deficiency. Chromatin immunoprecipitation followed by sequencing (ChIP-seq) reveals direct binding of URI to promoters of many iron-regulated genes, including bHLH38/39/100/101 but not FIT. While URI transcript and protein are expressed regardless of iron status, a phosphorylated form of URI only accumulates under iron deficiency. Phosphorylated URI is subject to proteasome-dependent degradation during iron resupply, and turnover of phosphorylated URI is dependent on the E3 ligase BTS. The subgroup IVc bHLH transcription factors, which have previously been shown to regulate bHLH38/39/100/101, coimmunoprecipitate with URI mainly under Fe-deficient conditions, suggesting that it is the phosphorylated form of URI that is capable of forming heterodimers in vivo. We propose that the phosphorylated form of URI accumulates under Fe deficiency, forms heterodimers with subgroup IVc proteins, and induces transcription of bHLH38/39/100/101. These transcription factors in turn heterodimerize with FIT and drive the transcription of IRT1 and FRO2 to increase Fe uptake.